Internal Locus of Control and Academic Self-Efficacy Influence on Academic Adjustment among College Students - Auliya, Nabilla Nur; Zaharuddin, Zaharuddin; Darmayanti, Kusumasari Kartika Hima (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2023)
Academic adjustment is a critical experience for university students in an educational setting. Students' ability to adjust with academic pressures will determine their level of success in reaching educational goals and academic development. As a result, it is critical to comprehend the psychological aspects that can influence a student's academic adjustment. This study examined the influence of internal locus of control and academic self-efficacy on academic adjustment among students at the Faculty of Psychology UIN Raden Fatah Palembang. This study involved (n=228) students selected using simple random sampling. The data was analyzed with IBM SPSS version 26 and Mplus version 7. Internal locus of control and academic self-efficacy significantly contribute to academic adjustment (R2 = 0.975). The increase in one point on internal locus of control and academic self-efficacy will impact academic adjustment. To improve students' academic adjustment, universities, especially academic departments, should focus on student locus of control and academic self-efficacy. They can approach learning problems better equipped and achieve their academic goals if they improve their internal locus of control and academic self-efficacy.